2004
DOI: 10.1126/science.1097920
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Conservation and the Eradication of Poverty

Abstract: It is widely accepted that biodiversity loss and poverty are linked problems and that conservation and poverty reduction should be tackled together. However, success with integrated strategies is elusive. There is sharp debate about the social impacts of conservation programs and the success of community-based approaches to conservation. Clear conceptual frameworks are needed if policies in these two areas are to be combined. We review the links between poverty alleviation and biodiversity conservation and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
705
1
26

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,061 publications
(740 citation statements)
references
References 21 publications
8
705
1
26
Order By: Relevance
“…In reality, most projects that seek to integrate conservation and development tend to be too ambitious (Brown 2003;Adam et al 2004), and success with integrated strategies is elusive (Adam et al 2004). A recent report of World Bank projects focusing on the integration of poverty reduction and biodiversity conservation revealed that only 16% made major progress on both objectives (Tallis et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In reality, most projects that seek to integrate conservation and development tend to be too ambitious (Brown 2003;Adam et al 2004), and success with integrated strategies is elusive (Adam et al 2004). A recent report of World Bank projects focusing on the integration of poverty reduction and biodiversity conservation revealed that only 16% made major progress on both objectives (Tallis et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two key factors that affect equitable and sustainable development are as follows: (i) failure to simultaneously address economic and environmental problems in the developing world (Adams et al 2004) and (ii) lack of an ecosystem services approach and a network that can provide strategic directions to address poverty and environmental degradation (Perrings et al 2011). …”
Section: Factors Affecting Equitable and Sustainable Developmentmentioning
confidence: 99%
“…Since extreme poverty and biodiversity hotspots are generally co-located, any intervention to alleviate poverty and address biodiversity loss requires understanding of the dynamics of ecosystem services on which livelihood of local communities depend (Adams et al 2004;DeClerck et al 2006;Barrett et al 2011). (Cohen 2010).…”
Section: Failure To Simultaneously Address Poverty and Environmentmentioning
confidence: 99%
See 2 more Smart Citations